Factors associated with intention of clinical pharmacists and candidates to provide pharmaceutical care: application of theory planned behaviour - OKUYAN, BETÜL (My University, 2023)
Abstract Background Postgraduate education programs in clinical pharmacy have become widespread in Türkiye. This study aimed to identify factors associated with the intention of Turkish clinical pharmacists and candidates (who were graduates and students of postgraduate clinical pharmacy programs) to provide pharmaceutical care. Methods This prospective observational study was conducted between June 2021 and May 2022. After searching relevant studies, an expert panel discussion, translation, cultural adaptation, and a pilot study developed a 52-item Turkish scale based on the Theory of Planned Behavior (TBP). Cronbach alpha for each construct was calculated after an explanatory factor and test–retest reliability analysis. An online survey link was sent to all graduates or candi‑ dates of postgraduate clinical pharmacy programs in Türkiye. After univariate regression analysis, the multiple linear regression model was performed. Results One hundred ffty-six participants completed the survey (response rate: 59.1%). The Cronbach’s alpha for atti‑ tude (9 items), subjective norm (6 items), perceived behavioural control (5 items), self-efcacy (6 items), intention (11 items) and past behaviour (15 items) were 0.945, 0.720, 0.751, 0.864, 0.934 and 0.955 respectively. The multiple linear regression analysis found a higher score of the subjective norm (p=0.016), a higher score of self-efcacy (p<0.001), younger age (p<0.001) and having PhD (p=0.038) were associated with increased intention score. Conclusions It was shown that higher self efcacy and positive beliefs of their peers and other healthcare profes‑ sionals were associated with their higher intention score for providing pharmaceutical care. Younger age and having a PhD were other factors associated with their intention to provide pharmaceutical care.
Keywords: The theory of planned behaviour; Pharmaceutical care; Clinical pharmacy